The Use of Monopoly-Like Game (MLG) to Promote Qualified Scores for Three Student Competencies (Jurnal Pendidikan IPA Indonesia, 2018)
Learning ideally accommodate to not only improve cognitive competencies but also social and psychomotor as well. In fact, many practices are still lack of aforementioned concern, learning about thermal energy and its flow for instance. It focuses mainly on cognitive scores which indicate whether students can pass the exam or not. Hence, this research aimed at describing the use of MLG to promote qualified scores for competencies students have to achieve based on curriculum 2013, namely, social attitude, psychomotor and cognitive competencies altogether. In doing so, one shoot case study design was employed and involved 15 students of grade 7th. The research results showed that the students gained scores for those competencies. Each of which was 3.50 – 3.85, 3.60 – 4.00, and 3.60 – 3.80 respectively. As such, it indicated that the game was successfully promoting qualifying scores for student competencies.